A CASE OF HERNIATION THROUGH THE FORAMEN OF WINSLOW IN WHICH LAPAROSCOPIC REDUCTION WAS CONVERTED TO OPEN LAPAROTOMY - NOJIMA, Hiroyuki; TASHIRO, Tsuguhiko; CHIKU, Tsuyoshi; SANO, Wataru; HASHIBA, Takahiro; OKAMOTO, Yosiaki (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2006)
We report a case of herniation through the foramen of Winslow diagnosed preoperatively, in which unsuccessful attempts of laparoscopic reduction of the hernia was converted to open laparotomy. A 46-year-old woman was admitted to the hospital because of epigastric pain and upper abdominal dilatation. She was diagnosed as having intestinal obstruction. Abdominal CT scan showed a dilated intestine in the omental bursa. Symptomatic remission could not be attained despite insertion of a long tube. Abdominal CT scan disclosed that the ileum was incarcerated through the foramen of Winslow into the lesser sac. We tried to reduce the herniation under the laparoscopy, but could not. Accordingly we converted the laparoscopic reduction to open laparotomy. Operative findings showed that a loop of the distal ileum by 22cm in length was incarcerated through the foramen of Winslow into the lesser sac. The foramen of Winslow which opened up to two fingers was not sutured and the bowel running was normal. Since the herniated bowel was viable, manual reduction was employed without performing intestinal resection.